NEWS JUNKIE OR ONLY ACCIDENTALLY INFORMED? AN IN-SITU STUDY ON SITUATIONAL TYPES AND INDIVIDUAL REPERTOIRES OF MOBILE NEWS ACCESS AMONG GERMAN YOUNG ADULTS. - Karnowski, Veronika; Knop-Huelss, Katharina; Olbermann, Zoe (AoIR Selected Papers of Internet Research, 2020)
Over the past three decades our media ecologies have changed substantially, not at least changing the ways in which we get in touch with the news. These changes have led both to high hopes for more equality in news access and a better-informed electorate, as well as fears of news avoidance, filter bubbles, and increasing knowledge gaps, with recent empirical evidence leaning towards rather pessimistic perspectives. However, most of the research to date focusses on one specific kind of news access, e.g., news consumption via social media, and its effects, neglecting the fact that users combine several ways to access the news throughout their daily lives, creating their individual media use repertoires. In order to disentangle these variances within our daily lives from differences between users, we need to analyze access to news on a situational level. Being meta-media, mobile media constitute an excellent microcosmos to study situational variability in news access. Hence, we investigated the situational types of mobile news access in young adults’ daily lives as well as their mobile news repertoires based on the previously identified situational access types. To do so, we conducted an experience sampling study among young adults in Germany. Our results highlight that differences within (mobile) news use should not only be studied as differences between people, but also as variances within users’ daily lives. For example, we see that no mobile news repertoire in our study solely relies on news access via intermediaries such as social media.